Konversi Waste Cooking Oil (WCO) Menjadi Biodiesel Menggunakan Katalis Basa Heterogen Na2O/Fe3O4 - Simarmata, Hery Fiza; Saputra, Edy; Irdoni, Irdoni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Heterogeneous catalysts in transesterification has been used to biodiesel production because have many advantages. This research aims to synthesize heterogeneous base catalyst Na2O/Fe3O4 which will be used in transesterification reaction for production of biodiesel. Catalyst Na2O/Fe3O4 was synthesized from sodium hydroxide (NaOH) and iron powder using wet impregnation method. The independent variables of this research are molar ratio of WCO/methanol 1:6, 1:8, 1:10, and loading catalyst Na2O/Fe3O4 3%, 4%, 5%-w WCO. These variables are to determine the yield crude biodiesel. Reaction temperature is 60°C (±2) for 2 hours, under stirring 300 rpm. The highest yield of biodiesel is 95.45% under the transesterification methanol/WCO molar ratio 1:10, loading catalyst 3%-w.Keywords: Biodiesel, esterification, catalyst, heterogeneous, transesterification, WCO